Penundaan Pembagian Waris: Suatu Tinjauan Teoretis dalam Kerangka Sistem Hukum di Indonesia - Maimanah, Maimanah; al-Amruzy, M. Fahmi; Arni, Arni; Faridah, Siti (Universitas Islam Negeri Antasari Banjarmasin, 2024)
Delays in the distribution of inheritance are common in the Banjar community, and these delays in the distribution of inheritance cause various problems, ranging from conflicts between heirs that cause family relationships to break down, neglected inheritance, to litigation between families in court. This paper intends to scrutinize why this delay in inheritance distribution occurs. To answer this, the author discusses it in the perspective of Laurence M. Friedman's Legal System Theory, this research uses qualitative research methods in the form of empirical legal research. Data were obtained through in-depth interviews and observations, then analyzed with interpretative descriptive analysis. From this research, it was found that the legal structure of delaying the distribution of inheritance, namely religious courts, judges, advocates and scholars do not have the authority to